2011
DOI: 10.1080/0312407x.2010.520087
|View full text |Cite
|
Sign up to set email alerts
|

Crafting Communities: Promoting Inclusion, Empowerment, and Learning between Older Women

Abstract: Crafting Communities: Promoting inclusion, empowerment and learning between older womenWhile social policy and planning documents are replete with ominous warnings about the cost of an ageing population, this article tells a different story about the productive and self sustaining networks that exist amongst older women in the community who do craftwork. From our research conducted in Victoria, Australia during 2007-2008 we discovered a resilient and committed group of older women quietly and steadily contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…Wider social inclusion of mature aged entrepreneurs in national and corporate programs and strategies, as well as a wider acceptance of mature-age entrepreneurship in the broader society, is needed (Clarkin et al, 2012). This can assist in overcoming possible social isolation, discrimination, and having the benefit of wider inclusion on the workforce and economy (Maidment & MacFarlane, 2011). Those who desire to continue to play an active role in the social economy can access more opportunities for interaction and social involvement, which can lead to a higher quality of life and overall life satisfaction (Maritz & Laferriere, 2016).…”
Section: Benefits Of Entrepreneurship and Selfemployment For Mature-amentioning
confidence: 99%
“…Wider social inclusion of mature aged entrepreneurs in national and corporate programs and strategies, as well as a wider acceptance of mature-age entrepreneurship in the broader society, is needed (Clarkin et al, 2012). This can assist in overcoming possible social isolation, discrimination, and having the benefit of wider inclusion on the workforce and economy (Maidment & MacFarlane, 2011). Those who desire to continue to play an active role in the social economy can access more opportunities for interaction and social involvement, which can lead to a higher quality of life and overall life satisfaction (Maritz & Laferriere, 2016).…”
Section: Benefits Of Entrepreneurship and Selfemployment For Mature-amentioning
confidence: 99%
“…Ces constats conduisent à identifier un premier défi pour les praticiens de la relation désireux de soutenir le bien-être et l'apprentissage tout au long de la vie : contribuer à la création de liens d'interdépendance et de lieux de participation significatifs propices aux apprentissages (Bélanger, 2015). Le soutien social et l'intégration dans des réseaux significatifs permettent de développer des liens d'entraide et de réciprocité qui contribuent au bien-être (Maidment et Macfarlane, 2011). Les praticiens de la relation sont donc invités à valoriser ces ressources que sont ces liens qui se développent entre les personnes et à remettre en question un discours où la valeur repose surtout sur des termes marchands (Maidment et Macfarlane, 2011).…”
Section: Des Défis Pour Les Praticiens De La Relationunclassified
“…Le soutien social et l'intégration dans des réseaux significatifs permettent de développer des liens d'entraide et de réciprocité qui contribuent au bien-être (Maidment et Macfarlane, 2011). Les praticiens de la relation sont donc invités à valoriser ces ressources que sont ces liens qui se développent entre les personnes et à remettre en question un discours où la valeur repose surtout sur des termes marchands (Maidment et Macfarlane, 2011). Ces derniers sont amenés à prendre une distance avec ce discours, combiné à la prégnance des thèses associées au néolibéralisme qui entraînent une plus grande responsabilisation dévolue aux individus pour améliorer leur sort et faire face à l'incertitude.…”
Section: Des Défis Pour Les Praticiens De La Relationunclassified
“…There seems to be a need for embodied interaction with the material world and to make things by hand as a departure from conventional paid work and domestic duties (Grace & Gandolfo, 2014;Jackson, 2010). It has also been found that the majority of craft practitioners continue their leisure through all stages of life and into old age (Kenning, 2015;Lamont & Ranaweera, 2019;Maidment & Macfarlane, 2011).…”
Section: Introductionmentioning
confidence: 99%